A GA-Based X-Filling for Reducing Launch Switching Activity toward Specific Objectives in At-Speed Scan Testing - MIYASE, Kohei; FURUKAWA, Hiroshi; KAJIHARA, Seiji; WEN, Xiaoqing; YAMATO, Yuta (IEICE Transactions on Information and Systems, 2011)
Power-aware X-filling is a preferable approach to avoiding IR-drop-induced yield loss in at-speed scan testing. However, the ability of previous X-filling methods to reduce launch switching activity may be unsatisfactory, due to low effect (insufficient and global-only reduction) and/or low scalability (long CPU time). This paper addresses this reduction quality problem with a novel GA (Genetic Algorithm) based X-filling method, called GA-fill. Its goals are (1) to achieve both effectiveness and scalability in a more balanced manner and (2) to make the reduction effect of launch switching activity more concentrated on critical areas that have higher impact on IR-drop-induced yield loss. Evaluation experiments are being conducted on both benchmark and industrial circuits, and the results have demonstrated the usefulness of GA-fill.